(3cJGH GdWHGFNs - (3CHh eMeO Hf GdeXaQ Hf fUQ Hf SJGQ GdhQGb, GdhQGbs
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdbgGQ Gdedc GdLHGQ SCdJ CWGd Gddg HbGAc Cf GDda cJGHkG CLeY ajg GdhGfkG ef GdCWYeI GdeUfhYI ddedhc hGdNdaGA hGdSGOI hGdQDSGA s
(3BNQgG (B:s
(3eeG GfJNHg Gdedhc hGdNdaGA hGdbOeGA ef Cgd GdaVd hGdeYQaI heG ajg GdefGaY hGdahGFO s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeI (B- (3U (B177 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK HGSJGfHhd (B(2143) s
Keywords: (3GdUfGYI hGdCWYeIs